Sunscreen lotions in the dermatological prescription: review of concepts and controversies - Addor, Flavia Alvim Sant'anna; Barcaui, Carlos Baptista; Gomes, Elimar Elias; Lupi, Omar; Marçon, Carolina Reato; Miot, Hélio Amante [UNESP] (Elsevier, 2022)
The skin is regularly exposed to several environmental aggressions, including solar radiation, whose biological effects can induce sunburn, dyschromia, skin aging and cancer. Among the photoprotection measures, sunscreens comprise a relevant part of the strategy aimed to prevent solar radiation damage and, for effective action, the patient must adhere to the product use and the latter, in turn, must follow technical parameters to promote adequate protection. This review article brings together the most current and relevant concepts about photoprotection for dermatological use, including the challenges for their formulation, the risks of certain photoprotective active substances for individual and environmental safety and the importance of stringency in determining the product efficacy, considering the regulatory aspects, highlighting relevant differences between Brazil and other countries. Thus, when assessing a sunscreen, not only the visual aspects and sensory perception will be immediately evaluated, but also the quality and suitability of the vehicle, the chemical composition of the formulation, the environmental risks, the photostability of the screening system, and the measurement of its protection spectrum. Technical knowledge of sunscreens can help dermatologists in this important role of educating patients about the best photoprotective strategies in each situation.
Keywords: Dermatology; DNA damage; Skin neoplasms; Solar radiation; Sun protection factor; Sunscreening agents; Ultraviolet rays